Reproductive biology of kawakawa, Euthynnus affinis (Cantor, 1849) in Eastern Indian Ocean - Rani Ekawaty; Irwan Jatmiko (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2018)
Kawakawa (Euthynnus affinis) is one of the economically important fish species for fishermen in Denpasar, Bali. The objective of this study was to analyze the reproductive biology of kawakawa such as the gonadal maturity level (GML), gonad maturity index (GMI) and the length proportion of the mature gonads 50% (L50) and 95% (L95) of kawakawa in the Eastern Indian Ocean. Fish samples were collected from the fishermen catch landed at Kedonganan Fishing Port (PPI), Bali from May to September 2016. The total of fish samples collected were 168 individual. Each individual species was measured their fork length (FL), individual weight, gonad weight and determination of gonadal maturity level. The data obtained were analyzed to determine GML, GMI and proportions of gonads mature. The results showed that the fork length ranged from 26-55 cm with an average of 38 cm and dominated by a 28 cm. The maturity level of fish gonads was dominated by GML III (38%), followed by GML II (26%), GML I (22%) and GML IV (14%), respectively. The average gonad maturity index was 0.558 with a range of 0.009-5.075. The length of gonad matured in proportion 50% and 95% was 48.4 cm and 55.7 cm, respectively. It is suggested to regulating in fishing capture of kawakawa so that 50% of the fish caught have spawned. Abstrak Tongkol komo (Euthynnus affinis) merupakan salah satu jenis ikan ekonomis penting bagi nelayan di Denpasar, Bali. Penelitian ini bertujuan untuk menganalisis biologi reproduksi ikan tongkol komo seperti tingkat kematangan gonad (TKG), indeks kematangan gonad (IKG) dan panjang proporsi matang gonad 50% (L50) dan 95% (L95) tongkol komo di Samudra Hindia Bagian Timur. Contoh ikan dikumpulkan dari hasil tangkapan nelayan yang didaratkan di Pangkalan Pendaratan Ikan (PPI) Kedonganan, Bali dari bulan Mei hingga September 2016. Jumlah contoh ikan yang dikumpulkan sebanyak 168 ekor, masing-masing diukur panjang cagak, bobot individu, bobot gonad dan penetapan TKG. Data yang diperoleh dianalisis untuk menentukan TKG, IKG dan proporsi matang gonad. Hasil penelitian diperoleh panjang cagak berkisar antara 26-55 cm dengan rata-rata 38 cm dan didominasi kelas panjang 28 cm. Tingkat kematangan gonad ikan didominasi oleh TKG III (38%), kemudian diikuti oleh TKG II (26%), TKG I (22%) dan TKG IV (14%). Rata-rata indeks kematangan gonad sebesar 0,558 dengan kisaran 0,009-5,075. Proporsi Panjang matang gonad 50% dan 95% berturut-turut adalah 48,4 cm dan 55,7 cm. Perlu dilakukan pengaturan penangkapan sehingga 50% ikan yang tertangkap sudah pernah memijah.